Squeezing atoms using a confinement potential : a thesis presented in fulfillment of the requirements for the degree of Master of Science in Mathematical Physics, Massey University, Albany, New Zealand - Coxe, Julianne Neilson (Massey University, 2010)
Understanding the complexities of the interior of planets and stars requires the help of analyzing the effects of high pressures on certain elements believed to be found within. The Hartree-Fock method uses the Schr¨odinger equation, Kummer’s differential equations and a confinement potential to simulate an atom being squeezed to high pressures. The Hartree-Fock method was used to calculate the total energies of atoms. After being compared to Gaussian03 and VASP, the results were deemed accurate. It was also observed that the pressure versus density data closely approximated those pairs found in outer space in the interiors of, for example, Jupiter.
Keywords: Planets; Hartree-Fock method; Energies of atoms; Confinement potential; Mathematical physics; Stars; Fields of Research::240000 Physical Sciences::240300 Atomic and Molecular Physics; Nuclear and Particle Physics, Plasma Physics::240301 Atomic and molecular physics